Determinants of perception of heartburn and regurgitation. Issue 3 (24th August 2005) - Bredenoord, A J; Weusten, B L A M; Curvers, W L; Timmer, R; Smout, A J P M
Abstract : Background and aim: It is not known why some reflux episodes evoke symptoms and others do not. We investigated the determinants of perception of gastro-oesophageal reflux. Methods: In 32 patients with symptoms suggestive of gastro-oesophageal reflux, 24 hour ambulatory pH and impedance monitoring was performed after cessation of acid suppressive therapy. In the 20 patients who had at least one symptomatic reflux episode, characteristics of symptomatic and asymptomatic reflux episodes were compared. Results: A total of 1807 reflux episodes were detected, 203 of which were symptomatic. Compared with asymptomatic episodes, symptomatic episodes were associated with a larger pH drop (p<0.001), lower nadir pH (p<0.05), and higher proximal extent (p<0.005). Symptomatic reflux episodes had a longer volume and acid clearance time (p<0.05 and p<0.002). Symptomatic episodes were preceded by a higher oesophageal cumulative acid exposure time (p<0.05). The proximal extent of episodes preceding regurgitation was larger than those preceding heartburn; 14.8% of the symptomatic reflux episodes were weakly acidic. In total, 426 pure gas reflux episodes occurred, of which 12 were symptomatic. Symptomatic pure gas reflux was more frequently accompanied by a pH drop than asymptomatic gas reflux (p<0.05). Conclusions: Heartburn and regurgitation are more likely to be evoked when the pH drop is large, proximal extent of the refluxate is high, and volume and acid clearance is delayed. Sensitisation of the oesophagus occurs by preceding acid exposure. Weakly acidic reflux is responsible for only a minority of symptoms in patients off therapy. Pure gas reflux associated with a pH drop ("acid vapour") can be perceived as heartburn and regurgitation.